No Efficacy of the Combination of Lopinavir/Ritonavir Plus Hydroxychloroquine Versus Standard of Care in Patients Hospitalized With COVID-19: A Non-Randomized Comparison - Gagliardini, Roberta; Cozzi-Lepri, Alessandro; Mariano, Andrea; Taglietti, Fabrizio; Vergori, Alessandra; Abdeddaim, Amina; Di Gennaro, Francesco; Mazzotta, Valentina; Amendola, Alessandra; D’Offizi, Giampiero; Palmieri, Fabrizio; Marchioni, Luisa; et al. (Frontiers in Pharmacology, 2021)
Objectives No specific treatment has been approved for COVID-19. Lopinavir/ritonavir (LPV/r) and hydroxychloroquine (HCQ) have been used with poor results, and a trial showed advantages of combined antiviral therapy vs. single antivirals. Aim of the study was to assess the effectiveness of the combination of antivirals (LPV/r, HCQ) or their single use in COVID-19 hospitalized patients vs. Standard of Care (SoC). Methods Patients >=18 years with SARS-CoV-2 infection, defined as positive RT-PCR from nasal/oropharyngeal (NP/OP) swab or positive serology, admitted at L. Spallanzani Institute (Italy) were included. Primary endpoint: time to invasive ventilation/death. Secondary endpoint: time to 2 consecutive negative SARS-CoV-2 PCR in NP/OP swabs. In order to control for measured confounders, a marginal Cox regression model with inverse probability weights was used. Results A total of 590 patients were included in the analysis: 36.3% female, 64 years (IQR 51-76), 91% with pneumonia. Cumulative probability of invasive ventilation/death at 14 days was 21.2% (95% CI 17.6, 24.7), without difference between SOC, LPV/r, HCQ, HCQ+LPV/r and SoC. The risk of invasive ventilation/death in the groups appeared to vary by baseline ratio of arterial oxygen partial pressure to fractional inspired oxygen (PaO2/FiO2). Overall cumulative probability of confirmed negative nasopharyngeal swabs at 14 days was 44.4% (95% CI 38.9, 49.9), without difference between groups. Conclusions In this retrospective analysis, we found no difference in the rate of invasive ventilation/death or viral shedding by different strategies, as in randomized trials performed to date. Moreover, even the combination HCQ+LPV/r did not show advantages vs. SoC.